Evaluation of temperature effect on cyclic fatigue resistance of nickeltitanium instruments in a double-curved canal: a comparative study - Jumaa, Zainab Mohammed; Shukri , Biland Mohammed Salim (Brazilian Dental Science, 2022)
Objective: To investigate the effect of room and body temperatures on cyclic fatigue resistance of three endodonticnickel-titanium rotary files: Hyflex EDM (HEDM) (Coltene/Whaledent, Switzerland), WaveOne Gold (WOG)(Dentsply Maillefer, Switzer), and EdgeOne Fire (EOF) (EdgeEndo, Albuquerque, New Mexico, USA) in a doublecurvedcanal. Material and Methods: In this study, Sixty NiTi rotary files were used. These files were dividedinto three groups (n = 20 for each group). Group A: HEDM (size 25, taper 0.08), group B: WOG (size 25, taper0.07), and group C: EOF (size 25, taper 0.07). Each group was subdivided into two subgroups (n=10 for eachsubgroup). One of the subgroup was subjected to cyclic fatigue test at room temperature (20±1°C), while theother subgroup was subjected to cyclic fatigue test at body temperature (37±1°C). These files were tested by usinga custom-made artificial canal with a double curvature (coronal curve: 60° curvature with 5 mm radius; apicalcurve: 70° curvature with 2 mm radius). All instruments were rotated according to the manufacturer instructionsuntil the fracture occurred by using electric endodontic motor (Wave One, Dentsply Maillefer, Ballaigues,Switzerland). The number of cycles to fracture (NCF) and the fractured fragment length (FL) were recordedfor each endodontic file. The data were gathered and statistically analyzed using shapiro-wilk test and two-wayANOVA test. The statistical significance was set at 0.05. Results: The NCF of WOG and EOF were significantlylower at body temperature as compared to room temperature (p0.05). At 20±1°C, the results showed a non-significantdifference between NCF of WOG and EOF (p>0.05), while the NCF of HEDM was significantly lower than theother groups (p0.05).Conclusion: The temperature has a significant effect on cyclic fatigue resistance of EOF and WOG, whereas noeffect was observed on cyclic fatigue resistance of HEDM. WOG and EOF had a comparable NCF, while HEDMhad a lower NCF than other groups at room temperature. At body temperature, all tested files have a comparableNCF. These results were attributed to the type of the alloy and heat treated that was used to manufacture theseendodontic files. The cyclic fatigue test should be done at body temperature.KEYWORDSBody temperature; Cyclic fatigue; EdgeOne fire; Hyflex EDM; WaveOne Gold.